Unusual coloration pattern in juveniles of Stegastes fuscus (Actinopterygii: Pomacentridae) - de Araújo, Maria Elisabeth; Maranhão, Henrique A.; Véras, Dráusio P.; Hazin, Fábio (Zootaxa, 2009)
The diversity of color patterns in reef fishes, associated with the investigation of areas that had never been studied before, has resulted in a growing number of new species being described (Rocha, 2004; Lima et al. 2005; Rocha et al. 2007). However, the contrary is also true and in some cases recognized species are in reality populations or subspecies with fragile diagnoses (Wiley, 1981). This seems to be the case for Stegastes fuscus and other species of the same genus. Stegastes trindadensis (Gasparini et al. 1999) was separated from S. fuscus because it presents a yellow area in the dorsal fin, during its juvenile phase. Nevertheless, Gasparini and Floeter (2001) recognized that S. trindadensis should be reclassified as a subspecies. Juveniles of S. fuscus with a different color pattern described for the species have been found in natural reefs of Porto de Galinhas and Tamandaré (B.P. Ferreira, pers. comm. 2007), as well as in shipwrecks located along the coast of Pernambuco, with records also for Paraiba (L.A. Rocha, pers. comm. 2007) and the southeastern Brazilian coast (Carvalho-Filho, 1999). Besides the bluish color with scintillating spots, these specimens also have a dorso-anterior band in yellowish and reddish colors (Fig. 1), which is not present on the common color pattern (Fig. 2). This color pattern was previously unknown for this species, and further genetic investigation is necessary to determine if it differs from the normal color morph. The authors thank Dr. George and Mathews Burguess for their suggestions, and Dr. L.A Rocha for the valuable discussion.